MONITORING AND E-COACHING AS THE COACHING ALTERNATIVE OF CERTIFIED MATHEMATICS TEACHERS OF SMP IN YOGYAKARTA - Sri Purnami, Agustina; Ekosiswoyo, Rasdi; -, Haryono; -, Fakhruddin (The Journal of Educational Development, 2015)
The existing studies have resulteda coaching model for certified mathematics teachersof junior high schoolusing Mathematics Coaching Program (MCP). In this coaching program, mathematics teachers were given the opportunity to convey, discuss, and solve the problems associated with learning mathematics. At the end of each meeting, the teachers were given the task to apply the learning model that is an alternative for the problem solution in the field. With this training, teachers implement training materials using learning model chosen in each school. As teachers implement the model, the monitoring was held by the trainers and principals. At that time, the teachers still received coaching using social networking media through email (e-coaching). By e-coaching, without waiting for the next meeting, the teachers received the necessary guidance. The coaching results indicate that the competence of junior high school math teacher who have been certified is improved. Before getting the coaching program, the mean value of teacher was at 43.695 which means âintermediateâ level. After getting the coaching program with MCP model, the mean value of professional competence becomes 73.2 which is âhighâ level After being tested using t-test, it is obtained that thit = 14,095. The result shows significant difference before and after the professional competence receivethe coaching program using MCP model which is followed by monitoring and e-Coaching (MEC). Regardingto the mean value, MCP model which is followed by the MEC is effective to be used to improve teachersâ performance, in this case is, to increase teachersâ professional competence.